Assessment of the visual behavior of volleyball players while blocking the ball: A study using a wearable camera - Umezaki, S.; Kida, N.; Nomura, T. (International Journal of Sport & Health Science, 2017)
The present study was conducted to analyze the visual behavior of volleyball players using a wearable camera, instead of the expensive eye trackers that have been employed to date. The position of the player`s forehead, i.e. the direction of the line of sight, was estimated approximately from the images recorded by the camera (pilot studies 1 and 2). We then examined differences in the player`s gaze shift patterns, ball pursuit time and initial spiker fixation when blocking the volleyball, as a function of experience in playing volleyball (main study). The results from pilot studies 1 and 2 indicated that the ball pursuit time from just after release of the ball by the setter and the time taken to fix on the spiker, i.e. the time between the blocker`s eyes leaving the ball and shifting to the spiker, was measured as accurately by the wearable camera as by using an eye tracker. The main study indicated that gaze shift pattern was separable into "gaze shift" (volleyball players, 100% and general sports players, 47.8 %) and "ball pursuit" types (general sports players, 52.2%) indicative of skills based differences. However, there was no detectable difference in the time when players shifted their sight from the ball, or in the time when they saw the spiker, according to skills based on prior volleyball experience. In conclusion, the present findings indicate that it is possible to estimate visual behavior during blocking tasks in volleyball using a less expensive wearable camera, rather than an expensive eye tracker.